Los valores morales para mejorar el comportamiento de los niños de primer grado paralelo “A” de la escuela de educación básica Miguel Riofrío de la ciudad de Loja sección vespertina, periodo 2017-2018 - Zhigui Gia, Jessica Veronica (2018)
The following research named as: "The moral values to improve the children’s behavior from the School of Basic education Miguel Riofrío of Loja city"; it has as general objective to determine the incidence of the moral values in the first-grade children’s behavior. The methods used were: the scientific, deductive, inductive, descriptive and statistical; the study population was based on 15 children, the diagnosis results showed that children have inadequate attitudes and behaviors within the classroom. Once the intervention proposal was applied, a post-test was applied which showed an improvement in children's attitudes and behaviors of the children subject to study; demonstrating that the activities inserted in the intervention proposal contributed to the practice of moral values, besides it also showed the need for an integral participation of all the educational actors in the different training workshops in the educational center, To socialize in them the importance of moral values.